Identification and characterization of a novel gene involved in glandular trichome development in Nepeta tenuifolia - Zhou, Peina; Dang, Jingjie; Shi, Zunrui; Shao, Yongfang; Sang, Mengru; Dai, Shilin; Yue, Wei; Liu, Chanchan; Wu, Qinan (Frontiers in Plant Science, 2022)
The Nepeta tenuifolia was a medicinal plant with useful bioactivities of antiviral, immunoregulatory, anti-inflammatory enriched in terpenoids and flavonoids. Its peltate glandular trichome (PGT) was a multicellular structure that regarded as the main deposit organ of monoterpenes, which may be an excellent model for investigating cell differentiation and development of glandular trichome (GT). The genes regulated glandular trichome has not been well-studied. Here, we identified a R2R3 MYB SBG9 family named as NtMIXTA1. The NtMIXTA1-overexpressed tobacco had longer, denser GTs. The virus-induced gene silencing (VIGS) of NtMIXTA1 resulted in lower PGT density, dramatically reduced monoterpenes content and related gene expression of monoterpene biosynthesis. Comparative transcriptomic and widely targeted metabolic analysis showed that silencing of NtMIXTA1 significantly influenced genes expression and metabolites production in biosynthesis of terpenoids, flavonoids and lipids. Our study laid a solid foundation for the mechanism of regulating GT development, and can be further understanding the regulatory network between GT development and metabolites flux and as well as provided a reference of studying plants of high medicinal value without genetic transformation.